Online School Future: Challenges and Expectations of Modern Education in Indonesia - Zulvia Trinova; Ali Mu'ammar Zainal Abidin; Khasanah Khasanah; Lela Susanty; Ulfa Maulani (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Rapid technological advances and integration into human life whose life is different, including learning and education will continue to be innovative and adaptable. This paper is intended to discuss the future of virtual schools in the face of challenges and opportunities to achieve modern and eye education in Indonesia. To that end, we have carried out a series of data collection with an electronic search system for several publications, both national and international, in scientific journals, books, and websites that actively discuss the problem of virtual learning in the future. After data collection, we further reviewed it systematically and included a coding system, in-depth interpretation, sharp evaluation and conclusion drawing that answered the research questions with high quality of validity. Based on the existing evidence in the discussion of understanding the results. So the result is a better future for online education in Indonesia along with rapid technological advances and efficiency in all fields. Now online education still needs state recognition and formalities so that more online schools appear in the country. Thus, these findings become important inputs for future educational studies with similar teaching activities.